Prolonged SARS-CoV-2 Illness in a Patient Receiving Ocrelizumab for Multiple Sclerosis. (8th April 2021) - Gibson, Elena G; Pender, Melissa; Angerbauer, Michael; Cook, Craig; Jones, Barbara; Spivak, Adam M; Spivak, Emily S; Swaminathan, Sankar
Abstract: We describe a case of prolonged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a patient receiving ocrelizumab for multiple sclerosis. Viral RNA shedding, signs, and symptoms persisted for 69 days with resolution after administration of convalescent plasma and antiviral therapy. This case suggests risk for persistent SARS-CoV-2 infection in patients treated with anti-CD-20 monoclonal antibodies and supports a role for humoral immunity in disease resolution.